The Changes İn Angle Kl. II/1 Malocclusions İn Long Term Duration - Orhan Hamamcı (Galenos Yayinevi, 1988)
In this study, developmental differences of Angle Kl. II/1 malocclusions were investigated in ten patients after 8 years follow up period. Teleradiographic examination of the patients were taken before and after puberty, the mean age was 9 and 17 years old respectively and tracing were made individually. Cephalometric x-ray analysis and superposition techniques were used for investigation. Since a variety of mandibuler and maxiller growth were observed in the different directions, at least 2-3 years follow up period were necessery for the successful treatment of these patients. Spontan improvement can't be espected in severe cases. In the mild cases some improvement can be seen with the elimination of the factor causing malformation by itself.